Short communication: Cotton cultivars with moderate resistance to African cotton mosaic virus - Alegbejo, M.D.=700 1 Onu, I.; Banwo, O.O.
(Es, En)
Ilus., 16 ref.
Keywords: GOáYPIUM HIRSUTUM; VARIEDADES; RESISTENCIA A LA ENFERMEDAD; VIRUS DE LAS PLANTAS; NIGERIA; ESPAÑA; AFRICAN COTTON MOSAIC VIRUS